Respuestas

2013-12-02T12:18:26+01:00

x + 2y = -  3          (1)
y + 2z = 7              (2)
z + 2x = 11            (3)

De (1)
             x = - 3 - 2y    (4)
(4) en (3)
            z + 2(- 3 - 2y) = 11
            z - 6 - 4y = 11
            z - 4y = 17       (5)
(5) x (-2)
            - 2z + 8y = - 34   (5.1)
somando (5.1) (2)
              2z + y = 7 
                   9y = - 27
                     y = - 27/9                     y = - 3
En (5)
          z - 4(-3) = 17
              z + 12 = 17                          z = 5
En (1)
              x + 2(-3) = - 3
              x = - 6 = - 3                         x = 3